2011
DOI: 10.1351/pac-con-11-07-02
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic oxidation of 5-hydroxymethylfurfural to 2,5-diformylfuran on supported vanadium oxide catalysts: Structural effect and reaction mechanism

Abstract: The structure–activity relationship and reaction mechanism for selective oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-diformylfuran (DFF) in toluene were studied on vanadium oxide domains on TiO2, Al2O3, Nb2O5, ZrO2, and MgO and with a wide range of VOx surface densities. The structures of these catalysts were characterized by X-ray diffraction (XRD), diffuse reflectance UV–vis spectroscopy (UV–vis DRS), and Raman spectroscopy, and their reducibility was probed by H2-temperature programmed reduction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 3 publications
1
35
1
Order By: Relevance
“…This is the first time that this kind of study of the leaching and homogeneous contribution of supported vanadium catalyst has been performed for this reaction 17. 32, 42…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This is the first time that this kind of study of the leaching and homogeneous contribution of supported vanadium catalyst has been performed for this reaction 17. 32, 42…”
Section: Resultsmentioning
confidence: 94%
“…To overcome these drawbacks, UV Raman spectroscopy was employed 32. The excitation laser wavelength was selected to 244 nm to obtain a resonance Raman effect.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important oxidized products of HMF is FDCA, which has huge prospective in the production of bio‐based polymer analogous to polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), as a substitute for the petroleum‐derived terephthalic acid . Moreover, the partially oxidized form of HMF, the 2,5‐diformylfuran (DFF) is also an important starting material used for the production of polymers, fungicides, pharmaceuticals and so on …”
Section: Catalytic Oxidation Of Biomass‐derived Furfural and Hmf Overmentioning
confidence: 99%
“…It was demonstrated that Cu(NO3)2 facilitates the generation of V V species from VOSO4 and a V V /V IV redox cycle was involved. Recently, Liu and coworkers [104] also found that HMF oxidation to DFF proceeds via the redox mechanism involving V V /V IV redox cycles and the reoxidation of V IV to V V by O2 was the rate determining step.…”
Section: Catalytic Oxidation Of Hmf To Dffmentioning
confidence: 97%